Those who stayed, 1922
1 online resource (264 pages)
Keywords: The year 1922 marks a major turning point in Eastern Mediterranean history, with the abolition of the Ottoman Sultanate concluding a long period of upheaval known as the "Eastern Question." As the empire gave way to European colonization and the nation-state model, its once multicultural societies were homogenized through violence, population transfers, and treaties. The liberal principle of national self-determination often led to devastating human costs, as populations were either massacred, forcibly exchanged, or reduced to "minorities" within new political entities.While scholarship has thoroughly documented the demographic changes that accompanied the post-Ottoman transition, this volume focuses on a less explored dimension: the agency of those labeled as minorities. It examines how these communities navigated their new reality within emerging nation-states or League of Nations mandates. Adopting a broad and situational understanding of "minority," it includes both legally defined groups and those marginalized in practice, such as Muslims in Western Thrace, Christians in Istanbul, Armenians in Jerusalem, Muslims in Serbia, and Jews in Salonica.The volume uses diverse methodologies-archival research, network analysis, microhistory, and translocal perspectives - to investigate the lived experiences of entrenched minorities. It offers new insights into both lesser-known and familiar minority groups, while engaging critically with existing literature. By emphasizing these groups' strategies and resilience, the volume challenges narratives dominated by violence and nostalgia, offering a more nuanced understanding of post-1922 Eastern Mediterranean history. It will appeal not only to scholars of minority studies but to anyone interested in the region's modern past.